Efficient extreme UV harmonics generated from picosecond laser pulse interactions with solid targets - Norreys, P; Zepf, M; Moustaizis, S; Fews, A; Zhang, J; Lee, P; Bakarezos, M; Danson, C; Dyson, A; Gibbon, P; Loukakos, P; Neely, D; et al. (1996)
The generation of high harmonics created during the interaction of a 2.5 ps, 1053 nm laser pulse with a solid target has been recorded for intensities up to 1019 W cm-2. Harmonic orders up to the 68th at 15.5 nm in first order have been observed with indications up to the 75th at 14.0 nm in second-order diffraction. No differences in harmonic emission between s and p polarization of the laser beam were observed. The power of the 38th high harmonic at 27.7 nm is estimated to be 24 MW.